Cgras2 controls growth and virulence through the regulation of intracellular cAMP level, cytoskeleton organization, and protein secretion in Colletotrichum gloeosporioides - Qianyi Xiao; Yi Zhang; Liping Feng; Hongli Luo; Bang An; Qiannan Wang (Phytopathology Research)
Abstract Fungal pathogens utilize intricate signaling networks to regulate growth, morphogenesis, and infection processes, enabling them to adapt to environmental cues and successfully colonize their hosts. Among these networks, the Ras signaling pathway has been extensively studied for its role in fungal morphogenesis and virulence. However, the specific contributions of Ras2 to key pathogenesis processes, such as cytoskeletal organization, appressorium formation, and protein secretion, remain poorly understood. Addressing this gap is critical to understanding the molecular mechanisms underlying fungal virulence and identifying potential targets for disease control strategies. Here, a Ras2 homologue (Cgras2) was identified in Colletotrichum gloeosporioides, a hemibiotrophic fungal pathogen responsible for anthracnose diseases in over 3200 plant species. Using a target deletion mutant ΔCgras2, we found that Cgras2 is essential for maintaining conidial germination polarity, cell division, and virulence. Knockout of Cgras2 also impaired appressorium formation and infection by disrupting cytoskeletal networks, including F-actin and septin rings, and by reducing turgor pressure, which is critical for penetration peg formation. Additionally, Cgras2 functions as an upstream regulator of the cAMP signaling pathway, as ΔCgras2 mutants exhibit reduced intracellular cAMP levels. Supplementation with exogenous cAMP partially rescued the formation of appressoria and the virulence in ΔCgras2 mutant, confirming the regulatory role of Cgras2 in cAMP signaling. RNA-seq analysis further revealed significant downregulation of membrane transporter-encoding genes in ΔCgras2 mutants, leading to disruptions in sugar and ion uptake. Secretome analysis demonstrated that Cgras2 also controls extracellular secretion of plant cell wall-degrading enzymes and other virulence factors by regulating the secretion process and genes involved in transcription. Enzymatic activity assays of extracellular hydrolases further confirmed that the absence of Cgras2 significantly impaired secretory capacity. Our findings establish the Cgras2 protein as a central regulator of fungal infection strategies by linking cytoskeletal organization, membrane transport, and protein secretion with Ras2 signaling. These insights provide a foundation for future research into Ras2-mediated signaling networks and identify Cgras2 as a promising target for controlling fungal diseases in plants.